Cuprophilia: Dye-sensitized solar cells with copper(I) dyes and copper(I)/(II) redox shuttles. (September 2018) - Karpacheva, Mariia; Malzner, Frederik J.; Wobill, Cedric; Büttner, Annika; Constable, Edwin C.; Housecroft, Catherine E.
Abstract: With a goal of designing dye-sensitized solar cells (DSCs) containing only Earth-abundant components to achieve sustainable energy conversion, DSCs with heteroleptic copper(I)-based dyes and homoleptic copper(I)/(II) redox shuttles have been investigated. By using a phosphonic acid anchor, and 4, 4′-dimethoxy-6, 6′-dimethyl-2, 2′-bipyridine as the ancillary ligand in the dye and in the electrolyte, a DSC photoconversion efficiency of 2.06% (38.1% relative to N719 set at 100%) was achieved. The results demonstrate the potential for all-copper-based DSCs, opening the way for further dye and electrolyte optimization. Graphical abstract: Highlights: All-copper dye-sensitized solar cells (DSCs) in which both the dye and the electrolyte comprise copper-diimine complexes. The use of Earth-abundant elements in the electrolyte in DSCs. Towards sustainable energy conversion.